Deforestation forecasts in the Legal Amazon using intervention models (Research, Society and Development, 2021)
In this paper, it was used the Box-Jenkins methodology to assess the historical deforestation data generated by PRODES in the Brazilian Legal Amazon region from 1988 to 2018, in order to acquire deforestation forecasts. Considering that the model achieved an acceptable performance, forecasts were estimated for the next seven years (2019 to 2023). If there is no significant intervention in the series, deforestation rates are expected to remain ranging from 7,559.97 km2 to 7,730.88 km2, with a mean around 7,625.12 km2. In the case of an intervention, these quantities may vary from 10,429.28 km2 to 28,669.75 km2, with a mean near to 16,766.71 km2, indicating an increase of 119% on deforestation rates. In this sense, this article reinforces the need for maintenance and expansion of the environmental governance structure for the Brazilian Legal Amazon, according to what has happened in the last decade, especially based on the instruments of Command and Control related, for example, to expansion of Conservation Units, institution of the Rural Environmental Registry (CAR), inducing land regularization, improvement of the detection and monitoring system of burning and deforestation, such as PRODES and DETER, and also ostensive operations to combat illegal deforestation governmental institutions.